Result of the Physiologic Pacing Registry, an international multicenter prospective observational study of conduction system pacing - Vazquez, Pablo Moriña; Mohamed, Uwais; Zanon, Francesco; Lustgarten, Daniel L.; Atwater, Brett; Whinnett, Zachary I.; Curila, Karol; Dinerman, Jay; Molina-Lerma, Manuel; Wiley, Jim; Grammatico, Andrea; Lee, Kwangdeok; et al. (Heart rhythm, 2023)
Conduction system pacing (CSP), including both left bundle branch area pacing (LBBAP) and His-bundle pacing (HBP) has been proposed as an alternative therapy option for patients with indication for cardiac pacing to treat bradycardia or heart failure. The purpose of this study was to evaluate implant success, safety, and electrical performances of HBP and LBBAP in the multinational Physiological Pacing Registry. The international prospective observational registry included 44 sites from 16 countries globally between November 2018 and May 2021. Of 870 subjects enrolled, CSP lead implantation was attempted in 849 patients. Subjects with successful CSP lead implantation were followed for 6 months (5 ± 2 months). CSP lead implantation was successful in 768 patients (90.4%). Implant success was 95.2% (239/251) for LBBAP and 88.5% (529/598) for HBP (P = .002). Procedural duration and fluoroscopy duration were comparable between LBBAP and HBP (P = .537). Capture threshold at implant was 0.69 ± 0.39 V at 0.46 ± 0.15 ms in LBBAP and 1.44 ± 1.03 V at 0.71 ± 0.33 ms in HBP (P <.001). Capture threshold at 6 months was 0.79 ± 0.33 V at 0.44 ± 0.13 ms in LBBAP and 1.59 ± 0.97 V at 0.67 ± 0.31 ms in HBP (P <.001). Pacing threshold rise ≥1 V was observed at 6 months in 3 of 208 (1.4%) of LBBAP and 55 of 418 (13.2%) of HBP (P <.001). Serious adverse events related to implant procedure or CSP lead occurred in 5 of 251 (2.0%) with LBBAP and 25 of 598 (4.2%) with HBP (P = .115). This large prospective multicenter study demonstrates that CSP is technically feasible in most patients with relatively higher implant success and suggests that, with current technology, LBBAP may have better pacing parameters than HBP. [Display omitted]